The NEURON book - Carnevale, Nicholas T.; Hines, Michael L. (Cambridge : Cambridge University Press, 2006)
The authoritative reference on NEURON, the simulation environment for modeling biological neurons and neural networks that enjoys wide use in the experimental and computational neuroscience communities. This book shows how to use NEURON to construct and apply empirically based models. Written primarily for neuroscience investigators, teachers, and students, it assumes no previous knowledge of computer programming or numerical methods. Readers with a background in the physical sciences or mathematics, who have some knowledge about brain cells and circuits and are interested in computational modeling, will also find it helpful. The NEURON Book covers material that ranges from the inner workings of this program, to practical considerations involved in specifying the anatomical and biophysical properties that are to be represented in models. It uses a problem-solving approach, with many working examples that readers can try for themselves.
Tour of the NEURON simulation environment -- Modeling perspective -- Expressing conceptual models in mathematical terms -- Essentials of numerical methods for neural modeling -- Representing neurons with a digital computer -- How to build and use models of individual cells -- how to control simulations -- How to initialize simulations -- How to expand NEURON's library of mechanisms -- Synaptic transmission and artificial spiking cells -- Modeling networks -- hoc, NEURON's interpreter -- Object-oriented programming -- How to modify NEURON itself.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Neurons -- Computer simulation; Neural networks (Neurobiology) -- Computer simulation